Биология и продуктивность массовых видов фитобентоса Черного моря - (:unkn) unknown (Киев : Наук. думка, 1974)
На основании наблюдений в аквариуме и в природе за ростом и развитием водорослей в различные сезоны вычислена продукция некоторых ведущих форм макрофитобентоса (цистозиры и филлофоры) в Черном море. Наибольшая продукция наблюдается в весенний и осенний периоды. Летом и зимой происходит снижение темпа роста у макрофитов. Темп продуктивности связан с циклами развития растений. В среднем у советских берегов Черного моря общая годовая продукция макрофитов достигает около 10 млн. т сырой массы.
Biology and production of mass species of the Black Sea phytobenthos
On the basis of observations of the algae growth and development in the aquarium and in nature during different seasons, the production is calculated for some macrophytobenthos principal forms (Cystoseira and Phyllophora) in the Black Sea. The greatest production is observed in the spring and autumn periods. In summer and winter there occurs a decrease in the growth rate of macrophytes. The productivity rate is connected with the development cycles of plants. On the average the total annual production of macrophytes at the Black Sea Soviet coast reaches 10 mill. t. of green mass approximately.